Canola Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C. (My University, 2000)
This publication contains information for a projected budged reflecting expected income and cost based on canola production practices in south central Kansas.
MF2421_2000_10
Keywords: MF2421; Crops; Economics; MF